2018
DOI: 10.1302/2046-3758.76.bjr-2017-0325.r2
|View full text |Cite
|
Sign up to set email alerts
|

Can patient-specific finite element models better predict fractures in metastatic bone disease than experienced clinicians?

Abstract: ObjectivesIn this prospective cohort study, we investigated whether patient-specific finite element (FE) models can identify patients at risk of a pathological femoral fracture resulting from metastatic bone disease, and compared these FE predictions with clinical assessments by experienced clinicians.MethodsA total of 39 patients with non-fractured femoral metastatic lesions who were irradiated for pain were included from three radiotherapy institutes. During follow-up, nine pathological fractures occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 26 publications
1
56
1
Order By: Relevance
“…However, to what extent the simulations were affected by the air artifact remains unclear, as the change in position in the gantry also played a role. In our previous patient study, we noted that air gaps induced a visibly larger artifact in the calibration phantom compared to the current results. Additionally, this artifact was only seen in scans made on a relatively old CT scanner (AcQSim CT, Philips Medical Systems, Eindhoven, The Netherlands).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, to what extent the simulations were affected by the air artifact remains unclear, as the change in position in the gantry also played a role. In our previous patient study, we noted that air gaps induced a visibly larger artifact in the calibration phantom compared to the current results. Additionally, this artifact was only seen in scans made on a relatively old CT scanner (AcQSim CT, Philips Medical Systems, Eindhoven, The Netherlands).…”
Section: Discussioncontrasting
confidence: 57%
“…The subject‐specific geometry and BMD are used as input for the FE models. Recently, studies using FE models showed promising results in discriminating patients with a low fracture risk from patients with a high fracture risk …”
mentioning
confidence: 99%
“…(48,49) This approach might also be applied to the context of cancer-induced bone disease, as demonstrated by Eggermont and colleagues who incorporated patient-specific finite-element analysis to predict fracture risk in individuals with bone metastasis. (50) The bone-remodeling process, involving bone formation and destruction by osteoblasts and osteoclasts, respectively, has been abstracted in mathematical models. The basic multicellular unit, which consists of models of these cells, has been studied in a normal context as well as in disease.…”
Section: Ex Vivo Bone Modelsmentioning
confidence: 99%
“…Similarly, attempts to assess bone mathematically have resulted in models describing alterations in physical properties such as bone strength, trabecular structure, permeability, and bone healing . This approach might also be applied to the context of cancer‐induced bone disease, as demonstrated by Eggermont and colleagues who incorporated patient‐specific finite‐element analysis to predict fracture risk in individuals with bone metastasis . The bone‐remodeling process, involving bone formation and destruction by osteoblasts and osteoclasts, respectively, has been abstracted in mathematical models.…”
Section: Introductionmentioning
confidence: 99%
“…This is often not practical in terms of computational effort and thus proxies are often used. For bone and implant materials this has included regions where strain concentrates excessively [17,18]; or the volume of elements within a defined region experiencing strain above the yield point for that material [4,6].…”
Section: Geometrymentioning
confidence: 99%